Danger Signs and 4T Risk Factors of Pregnant Women - Siti Mardianingsih; Asri Daniyati (Journal of Ners and Midwifery, 2023)
The number of cases of maternal death in 2020 was 122, an increase of 25 cases compared to 2019, which was 97 cases of maternal death. The highest number of maternal death cases was in West Lombok district with 43 cases. The maternal mortality rate in NTB Province has increased from 93.92 per 100,000 live births to 119.05 per 100,000 live births. When compared with the performance achievements in the RPJMN, the NTB province is still below the national target. The 4T factors (too old, too young, too closely spaced between pregnancies and too many children) can increase cases of complications in the mother. Birth interval between one child and another child of less than 2 years can increase the risk of maternal death. Delivery at intervals of less than 24 months (too often) is a high-risk group for postpartum hemorrhage. This research aimed to determine the risk factors experienced by pregnant women so that prevention can be taken to prevent maternal death during childbirth. The research method used a quantitative analytical observational with a Focus Group Discussion (FGD) approach. The research results showed that pregnant women did not understand the danger signs and risk factors for 4T, so that pregnant women are able to take preventive measures. Apart from that, this research also provides anticipatory solutions so that pregnant women and their husbands can avoid further complications related to the risks of 4T. This research concludes that the understanding of pregnant women and their husbands regarding the danger signs and risks of 4T has increased so that they are able to know the mother's condition during pregnancy and are able to plan and have a healthy pregnancy.